2008
DOI: 10.1139/x08-053
|View full text |Cite
|
Sign up to set email alerts
|

Fire history of pinyon–juniper woodlands at upper ecotones with ponderosa pine forests in Arizona and New Mexico

Abstract: We used maps of fire evidence, fire scar dendrochronology, forest age-structure analysis, and landscape analysis to investigate fire history at pinyon pine ( Pinus edulis Engelm.) – juniper ( Juniperus osteosperma (Torr.) Little, Juniperus scopulorum Sarg.) woodland – ponderosa pine ( Pinus ponderosa P. & C. Lawson) forest ecotones in Arizona (Tusayan) and in New Mexico (Canjilon). Results showed that charred trees were not evenly distributed across vegetative communities but were significantly (p < 0.0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
37
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 48 publications
(40 citation statements)
references
References 16 publications
2
37
1
Order By: Relevance
“…While the ecological, aesthetic, and recreational value of these ponderosa pine populations has recently been recognized with the creation of many new protected areas (receiving ''wilderness '' status in 2004[United States Senate 2004), dendroecological studies of fire regime in Nevada's Great Basin have focused mainly on pure pinyon-juniper woodlands (Py et al 2006, Bauer and. In Arizona and New Mexico, wildfires recorded by ponderosa pine fire scars did not generally spread to adjacent pinyon-juniper woodlands (Huffman et al 2008), but at Mt. Irish the two species are effectively mixed together, hence the forest type and associated fuel characteristics would not be different enough to alter stand-wide fire regime The fire-climate connection presented by the pyroclimatic 'dry' and 'wet' scenarios was developed prior to, and independently of, the fire history reconstruction.…”
Section: Discussionmentioning
confidence: 99%
“…While the ecological, aesthetic, and recreational value of these ponderosa pine populations has recently been recognized with the creation of many new protected areas (receiving ''wilderness '' status in 2004[United States Senate 2004), dendroecological studies of fire regime in Nevada's Great Basin have focused mainly on pure pinyon-juniper woodlands (Py et al 2006, Bauer and. In Arizona and New Mexico, wildfires recorded by ponderosa pine fire scars did not generally spread to adjacent pinyon-juniper woodlands (Huffman et al 2008), but at Mt. Irish the two species are effectively mixed together, hence the forest type and associated fuel characteristics would not be different enough to alter stand-wide fire regime The fire-climate connection presented by the pyroclimatic 'dry' and 'wet' scenarios was developed prior to, and independently of, the fire history reconstruction.…”
Section: Discussionmentioning
confidence: 99%
“…Weather data were obtained from the Jemez Springs National Climatic Data Center cooperative weather station (CO-OP ID 294369-2) (NCDC 2011) and were extrapolated across sites [62,63]. Historical fire frequency and size distributions were derived from fire history studies for southwestern ecosystems [18,[64][65][66][67][68][69][70][71][72], including local studies [41,44,73]. Vegetation species parameters were gleaned from literature, previous FireBGCv2 projects [57][58][59]66,74], and field data.…”
Section: Study Areasmentioning
confidence: 99%
“…Vegetation species parameters were gleaned from literature, previous FireBGCv2 projects [57][58][59]66,74], and field data. We adjusted fire size and frequency parameters until the model simulated landscape fire return intervals that were consistent with available fire history records [18,[64][65][66][67][68][70][71][72]75]. We adjusted biological tree species parameters (e.g., shade tolerance, growing degree days, cone crop probability, bark thickness) until modeled spatial distributions and individual species basal area characteristics matched published estimates for southwest vegetation communities under non-managed conditions (e.g., without suppression, logging, or other activities) [69,[76][77][78].…”
Section: Study Areasmentioning
confidence: 99%
“…Fire scars were also found on piñ on trees at the ecotone between an open ponderosa pine forest and a piñ onjuniper woodland in south-central New Mexico (Muldavin et al 2003); again, however, tree-age data were not sufficient to confidently reconstruct the spatial patterns of fire spread within the piñ on-juniper woodland. Huffman et al (2008) recently sampled fire scars and ages of all tree species throughout two study sites located at ecotones between piñ on-juniper and ponderosa pine forests in northern Arizona and New Mexico; they concluded that the historical fires documented in the ponderosa pine forests generally did not spread through the adjacent piñ on-juniper portions of the study areas. A major reason why low-severity fires apparently are unimportant in most piñ on and juniper vegetation is that the fuel structure, especially in persistent woodlands and in wooded shrublands, is not typically conducive to a spreading, low-severity fire that would spread via fine fuels without killing the dominant trees or shrubs.…”
Section: Site Conditionsmentioning
confidence: 99%